Integration of Maja Labo Dahu in Case-Based Learning to Strengthen Political Awareness of Students in Anti-Corruption Education from a Gender Perspective - Ibnu Khaldun; Nurwahidah Nurwahidah; Wiwi Maulida Rosulia; Ibnu Dzar Al Bimawi (Universitas Medan Area, 2026)
This study evaluates the effectiveness of integrating Maja Labo Dahu (MLD) honesty, self-control, and courage to report into Case-Based Learning (CBL) to strengthen political Awareness, anti-corruption intentions, and readiness to act among students, as well as to assess gender moderation and process mechanisms. An explanatory mixed-methods Design was employed through a quasi-experimental pre–post study with cluster randomization at the class level (CBL–MLD vs standard CBL). The BOPPPS–CBL syntax was enriched with SAO mapping, reason-giving, and dialogic role-play/World Café forums. T0–T1–T2 measurements were analyzed using ANCOVA and multilevel models, accompanied by process regression and qualitative triangulation. Results showed that the intervention outperformed the control group across all outcomes, with effects persisting at follow-up. Manipulation checks confirmed higher MLD internalization without differences in exposure time. Condition×gender interactions were detected: political awareness gains were relatively larger among males, while increases in anti-corruption intentions and readiness to act were more substantial among females. Process analysis identified value internalization as the primary driver of change, followed by equal participation and implementation fidelity. In conclusion, CBL–MLD is effective, replicable, and auditable, with curricular implications for standardizing value-based case drivers, reason-giving protocols, safe dialogic facilitation, and gender-sensitive strategies.